Safer and Performing Energetic Materials Based on Polyaniline-Doped Nanocomposites. Issue 2 (3rd April 2017) - Gibot, Pierre; Bach, Arnaud; Vidal, Loic; Schnell, Fabien; Gadiou, Roger; Spitzer, Denis
ABSTRACT: Nanothermites, combining a fuel with an oxidizer at the nanoscale, represent a class of energetic material that has been attracting increasing attention over the past decade. This intensive interest is due to their tuneable pyrotechnic performance, making the materials promising candidates for ordnance applications. However, the extreme mechanical and electrostatic sensitivities of energetic composites make handling them hazardous. In this study, a realistic desensitization method is suggested via the addition of polyaniline while maintaining an interesting combustion velocity in contrast to the literature values. This investigation claims a major scientific breakthrough in the preparation of safer energetic nanocomposites.